THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION AND INNOVATION CAPABILITY ON THE COMPETITIVENESS OF MSMEs AND ITS IMPACT ON MARKETING PERFORMANCE OF MSMEs IN LHOKSEUMAWE CITY - Muhammad Hayani; Rusydi Abubakar; Heriyana; Ikramuddin; Darmawati; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research examines the influence of entrepreneurial orientation and innovation capability on the competitiveness of MSMEs and their impact on the marketing performance of MSMEs in Lhokseumawe City. The sample in this study was 133 active MSMEs and business owners. Data collected through questionnaires were analyzed using a data analysis method using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The research results show that entrepreneurial orientation and innovation capability have a significant effect on competitiveness and marketing performance. And competitiveness has a direct effect on marketing performance. Then, in testing the indirect effect of competitiveness, it was found to act as a partial mediating variable in the relationship between entrepreneurial orientation and innovation capability on marketing performance. It is hoped that the results of this research will be important information for the government and MSME managers in Lhokseumawe City in order to create policies for the development of micro, small and medium enterprises.